Damaged : Childhood Trauma, Adult Illness, and the Need for a Health Care Revolution - Maunder, Bob (Bob G.); Hunter, Jon, 1958- (Book collections on Project MUSE., 2021)
"We need a revolution in care. Damaged tells the painful yet inspiring story of a dedicated psychiatrist and his most challenging patient. In the authentic voices of Dr. Robert Maunder and his patient, Isaac, we hear how childhood trauma harms Isaac's health for the rest of his life. Providing readers with a window into the private world of long-term psychotherapy, we also see how deeply patients can affect the doctors who care for them. Dr. Maunder and his friend and colleague, Dr. Hunter, vividly demonstrate how the caring collegiality between doctors can significantly improve the medicine they practice. Through an honest retelling of interactions between doctors and patients, Damaged makes the case that health care would be both more compassionate and more effective if its practitioners acknowledged the role of trauma in the lives of patients. Above all, Damaged recognizes the need for change in our medical system and urges those who know, love, and treat people like Isaac to be kind, to be empathetic, and to take action."--